Information technology infrastructure project success criteria within the financial services sector in South Africa - Oosthuizen, Jacques (My University, 2017)
Project management, despite a growth in both maturity as a profession and increasing popularity as a means of successfully implementing organisational change initiatives, still experiences an unreasonably high project failure rate. At the same time, many projects are rated as failures while still delivering value, while others are seen as successful, without delivering substantial value. The aim of this study is to identify the key stakeholders involved in project success evaluation and the metrics that they hold most valuable, with the aim of identifying possible gaps which would assist in increasing both the successful delivery rate as well as the value delivered by these projects. The study focuses on the IT infrastructure area within one of the four major South African banks specifically. A review of available literature identified an extensive list of stakeholders and potential metrics, which were consolidated into a survey and presented to 76 respondents out of which 29 valid responses were obtained. Respondents were asked to identify how they perceived their role in project evaluation in relation to the stakeholder list presented, and evaluate each of the success metrics in terms of perceived value. The results indicate an opportunity for the stakeholder roles for projects within the IT infrastructure space to be consolidated to a fair degree. It also shows overwhelming support for a wide variety of metrics across both operational and strategic categories to be utilised in determining project success, indicating the need for an holistic view of project success that links the project scope to organisational strategy, and a need for project management offices to expand their methodologies and project life-cycle to accommodate these requirements.
MBA(Thesis)
MBA(Thesis)
Keywords: Project management -- South Africa. Financial services industry -- South Africa.